Mindfulness, perceived social support, and suicidal ideation among Chinese adolescents: the mediating role of self-compassion - Zhang, Shining; Ren, Yanzhen; Zeng, Haiping; Rong, Donghuan; Ren, Hanlin; Jiang, Tingyun; Fang, Yuan (Frontiers in Psychiatry, 2025)
ObjectivePrevious studies have demonstrated that mindfulness and perceived social support are protective factors against suicide. However, the potential common mechanisms underlying these relationships remain unclear. This study aimed to examine the associations between mindfulness, perceived social support, and suicidal ideation, and to explore the mediating role of self-compassion in these relationships among a sample of adolescents in China.MethodsA total of 1709 adolescents (M_age= 15.06, SD_age= 1.51) were recruited from one junior high school and one senior high school in Zhongshan, China. Mindfulness, perceived social support, suicidal ideation and self-compassion were assessed using self-report questionnaires. Structural Equation Modeling (SEM) was used to estimate the relationships between the variables.ResultsMindfulness and perceived social support were both positively associated with self-compassion, which in turn was negatively associated with suicidal ideation. Moreover, self-compassion partially mediated the relationship between mindfulness and suicidal ideation (indirect effect = -0.12, 95% confidence interval [CI] [-0.15, -0.08]), as well as the relationship between perceived social support and suicidal ideation (indirect effect = -0.08, 95% CI [-0.11, -0.06]).ConclusionsMindfulness and perceived social support were associated with lower levels of suicidal ideation, and these associations were partially explained by self-compassion, suggesting that self-compassion may act as a shared mediator. Interventions that strengthen mindfulness, perceived social support, and self-compassion—such as mindfulness-based supportive group interventions or compassion-focused therapy—may be particularly beneficial for adolescents experiencing suicidal ideation.